Profiling Blautia at high taxonomic resolution reveals correlations with cognitive dysfunction in Chinese children with Down syndrome - Hou, Xueyu; Wu, Na; Ren, Shimeng; Wang, Xinjuan; Mu, Qing; Zhang, Yang; Wang, Shan; Yu, Weidong; Guo, Jingzhu (Frontiers in Cellular and Infection Microbiology, 2023)
Down syndrome (DS), the presence of a supernumerary chromosome 21, is associated with cognitive dysfunction caused by early neurodegenerative processes. Alterations in the gut microbiota were observed in Chinese children with DS, and the genus Blautia was associated with cognitive function in these children. Therefore, it is crucial to understand the detailed composition of this group at the species level and to explore the effect of specific species on cognitive function. In this study, Blautia-specific amplicon sequencing was conducted to identify the specific Blautia species in 15 children with DS and 15 matched healthy children. The taxonomic analyses suggested that the Blautia taxa were clustered by disease status. The diversity of Blautia at the species level differed between DS patients and healthy controls, with the abundances of Blautia massiliensis and Blautia argi decreasing in DS children, while Blautia faecis was increased. Acetic acid, one of the metabolites of Blautia, was significantly reduced in the DS group. Of particular interest, Kyoto Encyclopaedia of Genes and Genomes analysis revealed decreased modules related to starch and sucrose metabolism and glycolysis. In addition, B. argi was positively related to DS cognitive scores, and B.faecis was negatively related to cognitive function, implying its role on the DS cognitive impairments. Our study has important implications for understanding the important effects of specific species of Blautia on cognitive function and thus possibly provides a new strategy for future studies of cognitive improvement in individuals with DS.